Inclusive leadership in hospitality: a driver of social inclusion? - Vassou, Chrystalla; Theocharous, Antonis L.; Zopiatis, Anastasios (My University, 2024)
Purpose: The importance of inclusive leadership has been recognized by scholars and practitioners alike. However, the ways in which inclusive leadership can be achieved and implemented in hospitality seem to be unclear. In order to answer how inclusive leadership can be put into practice in hospitality, this paper explores (1) employees' and managers' perceptions of inclusion and (2) diversity practices in hotel organizations. Design/methodology/approach: By espousing a qualitative methodology, semi-structured interviews with management representatives, as well as local and foreign employees of 4- and 5-star hotel organizations, were utilized in order to identify what inclusive leadership looks like in theory and in practice. Data were analyzed via thematic analysis and the utilization of the NVivo software. Findings: Findings suggest that an inclusive leader should be caring and respectful, pursue fair treatment, support employee development, express employee appreciation and recognize their role in social inclusion more widely. Originality/value: This original work reduces the research-practice gap in the field of diversity management by providing succinct recommendations to hospitality managers in the form of an adaptable best practice framework. The diagrammatic framework includes the values related to inclusive leadership as they emerged, as well as the practices through which each theme could be enacted.
Keywords: Diversity management; Foreign labor; Hospitality industry; Inclusive leadership; Social inclusion